2020
DOI: 10.2147/idr.s256922
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical and Molecular Epidemiologic Characteristics of Ceftazidime/Avibactam-Resistant Carbapenem-Resistant <em>Klebsiella pneumoniae</em> in a Neonatal Intensive Care Unit in China</p>

Abstract: Background: Ceftazidime/avibactam (CZA)-resistant carbapenem-resistant Klebsiella pneumoniae (CRKP) infections occur in adults worldwide but are rarely observed in neonates. We evaluated the activities of CZA against CRKP and described the clinical and molecular epidemiology of CZA-resistant CRKP in a NICU prior to CZA approval in China. Methods: A laboratory-based surveillance of CRKP was conducted from July 2017 to June 2018. Clinical data were initially reviewed. Antimicrobial susceptibility was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Due to express carbapenemase and extended-spectrum β-lactamase, CR-KP strains are resistant to most general antibacterial drugs [ 30 ]. Here, the antimicrobial susceptibility testing showed that all the CR-KP strains were highly or completely resistant to general antibacterial drugs, such as piperacillin-tazobactam, cefoxitin, cefepime, aztreonam, amikacin, gentamicin, tobramycin, sulfamethoxazole and cefperazone-sulbactam, while the resistance rate to ceftazidime/avibactam was relatively low, accounting for 26.1%, which is higher than the results of Zhou et al [ 31 ]. As reported in previous studies, colistin and tigecycline were still a good choice for the treatment of CR-KP infection [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Due to express carbapenemase and extended-spectrum β-lactamase, CR-KP strains are resistant to most general antibacterial drugs [ 30 ]. Here, the antimicrobial susceptibility testing showed that all the CR-KP strains were highly or completely resistant to general antibacterial drugs, such as piperacillin-tazobactam, cefoxitin, cefepime, aztreonam, amikacin, gentamicin, tobramycin, sulfamethoxazole and cefperazone-sulbactam, while the resistance rate to ceftazidime/avibactam was relatively low, accounting for 26.1%, which is higher than the results of Zhou et al [ 31 ]. As reported in previous studies, colistin and tigecycline were still a good choice for the treatment of CR-KP infection [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Up to now, only one KPC-2 and IMP-4 co-producing CRKP isolate and one strain harbored bla KPC-2 and bla NDM-5 have been identified from children. 26 , 27 To our knowledge, this is the first report of the dissemination of Klebsiella pneumoniae coproducing KPC-2 and IMP-4 clones among children. Something of concern is that these two pediatric patients died of severe lung infection, which suggests that the Klebsiella pneumoniae isolates coproducing two carbapenemases may pose a significant health risk to pediatric patients.…”
Section: Discussionmentioning
confidence: 81%
“…However, early susceptibility testing is still essential to determine the proper treatment as incidences of CAZ-AVI resistant CR-KP have been previously reported. 16 …”
Section: Discussionmentioning
confidence: 99%